2019
DOI: 10.1093/tas/txz011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corn silage moisture at harvest on performance of growing steers with supplemental rumen undegradable protein, finishing steer performance, and nutrient digestibility by lambs1

Abstract: Abstract Three experiments evaluated delaying corn silage harvest, silage concentration, and source of supplemental protein on performance and nutrient digestibility in growing and finishing diets. Experiment 1 used 180 crossbred yearling steers (body weight [BW] = 428; SD = 39 kg) to evaluate corn silage dry matter (DM) (37% or 43%) and replacing corn with silage (15% or 45% of diet DM) in finishing diets containing 40% modified distillers grains with solubles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(65 reference statements)
4
5
0
Order By: Relevance
“…The results of this experiment align well with previous work reporting that increased inclusion rates of corn silage in finishing cattle diets result in reduced ADG and G:F ( Goodrich et al, 1974 ; Gill et al, 1976 ; DiCostanzo et al, 1997 , 1998 ; Burken et al, 2017a , 2017b ; Hilscher et al, 2019 ). This would be expected when corn silage replaces corn grain such as in this experiment because of the lesser NE g for corn silage compared with corn grain ( Owens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this experiment align well with previous work reporting that increased inclusion rates of corn silage in finishing cattle diets result in reduced ADG and G:F ( Goodrich et al, 1974 ; Gill et al, 1976 ; DiCostanzo et al, 1997 , 1998 ; Burken et al, 2017a , 2017b ; Hilscher et al, 2019 ). This would be expected when corn silage replaces corn grain such as in this experiment because of the lesser NE g for corn silage compared with corn grain ( Owens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 89%
“…Over the entire trial G:F was improved by 19% for the 5.5% RUP compared to 0.4% RUP treatment. This is consistent with data presented by Hilscher et al (2019) , reporting a linear increase in both ADG and G:F as supplemental RUP was increased in a corn silage growing diet from 0% to 4.2% (DM basis). Felix et al (2014) also reported increased ADG, final BW, and G:F in corn silage growing diets supplemented with RUP sources (dried distillers grains with solubles or soybean meal) compared to diets supplemented with only urea.…”
Section: Resultssupporting
confidence: 92%
“…Marbling score was quadratic ( P = 0.04) with cattle fed 14 CS having the greatest marbling score, 80 CS was intermediate but similar to 14 CS, and 47 CS was least. Hilscher et al (2019) reported no difference in LM area or marbling score when cattle were fed 15% or 45% CS, but observed lower final BW for cattle fed 45% CS when cattle were fed the same number of days.…”
Section: Resultsmentioning
confidence: 92%
“…In both groups, ADG and G:F linearly decreased with increase inclusion of CS. Hilscher et al (2019) reported a decrease in ADG when CS inclusion was increased from 15% to 45% of diet DM, but no difference in DMI. A study by Peterson et al (1973) evaluated cattle fed inclusions of CS at 28.6%, 57.1%, and 85.7% and cattle were fed a range of 172–227 days on feed.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation